Effect of Environmental Factors on Benthic Invertebrate Community in Nong Han Lake, Sakon Nakhon Province - Sangmek, Pichasit; Hatachote, Sittichai (Recent Science and Technology, 2021)
Study on benthic invertebrate community and related water and sediment quality in Nong Han Lake, Sakon Nakhon Province was conducted 3 times during October 2016 to June 2017. The result found 27 families from 3 phyla of benthic animals, dominated by Chironomid larva. The lowest density of benthic invertebrate was found in June 2017, in the range of 0-147 individual m-2 (averaged 28 individual m-2) and the highest in February 2017, in the range of 12-366 individual m-2 (averaged 95 individual m-2). Water quality was appropriate to the livelihood of aquatic animals except in many areas in June 2017, while high level of sediment organic matter was found in all seasons, and some areas had high sulfides accumulation. The results showed that the density of benthic invertebrates was significantly positive correlated with dissolved oxygen and negative correlated with sediment total organic matter (p<0.05).